Longitudinal MRI-PDFF Quantification of Hepatic Steatosis Reversibility During SGLT2-Inhibitor versus GLP-1 Receptor Agonist Therapy: A Prospective Cohort Study - Arsan Saliha; Dedi Sucipto; Mischa Chantal Adella; Ericca Dominique Perez (Sriwijaya Journal of Radiology and Imaging Research, 2025)
Introduction: Precise quantification of hepatic steatosis is central to managing metabolic dysfunction-associated steatotic liver disease (MASLD). MRI proton density fat fraction (MRI-PDFF) has displaced biopsy as a reproducible biomarker, yet real-world comparative monitoring data and formal early-response prediction remain scarce in Indonesian practice. We quantified steatosis reversibility on serial MRI-PDFF during SGLT2-inhibitor versus GLP-1 receptor agonist therapy and tested whether an early scan predicts response. Methods: In this prospective cohort at a tertiary hospital in Palembang, Indonesia, 90 adults with MASLD (baseline PDFF ≥5.5%) were grouped by prescribed therapy (SGLT2i, n=45; GLP-1 RA, n=45) and imaged at baseline, Month 3 and Month 6 on a 3.0 T scanner using a confounder-corrected 3D multi-echo spoiled gradient-echo sequence. Two blinded radiologists measured PDFF across Couinaud segments V/VI/VIII; response was a ≥30% relative reduction. Analyses (STARD 2015) included linear mixed-effects modelling, κ and intraclass correlation, ROC (DeLong), likelihood ratios and multivariable logistic regression. Results: PDFF fell in both arms (both p<0.001; partial η²=0.66 and 0.79). Responder rate was 75.6% (95% CI 61.3–85.8) with GLP-1 RA versus 40.0% (27.0–54.5) with SGLT2i (OR 4.64; p=0.001). A Month-3 decline ≥16.9% predicted Month-6 response with AUC 0.895 (0.823–0.967), sensitivity 96.2%, specificity 78.9%, LR+ 4.57, LR− 0.05. Inter-reader agreement was near-perfect (ICC 0.986; κ 0.861). GLP-1 RA therapy and higher baseline PDFF independently predicted response. Conclusion: Serial MRI-PDFF reliably quantified pharmacologically-induced steatosis reversibility, with GLP-1 RA producing greater fat loss and an early scan accurately triaging responders. MRI-PDFF is a robust, decision-useful monitoring biomarker deployable in tertiary settings.